1987
DOI: 10.1039/p29870000405
|View full text |Cite
|
Sign up to set email alerts
|

Ligand coupling within σ-sulphurane intermediates formed in the reaction of benzyl 2-pyridyl and related sulphoxides with Grignard reagents

Abstract: c tro comm unica ti0 ns, C h of uga o ka, C h o f us hi, Tokyo 182, Japan The reaction of benzyl or 1 -phenylethyl 2-pyridyl sulphoxide (1) or (18) with a Grignard reagent was found to give the ligand-coupling product, i.e., 2-benzylpyridine or 2-(1 -phenylethyl)pyridine (2) or (22) in excellent yield. This coupling reaction was found to proceed within the o-sulphurane formed as an intermediate upon treatment of benzyl2-pyridyl and related sulphoxides with a Grignard reagent. The stereochemical course of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 5 publications
2
17
0
Order By: Relevance
“…Interestingly, Seyferth et al carried out similar reactions using both cisand trans-propenyllithium reagents and obtained only cisand trans-propenylbenzenes, respectively [8]. This observation is in accordance with our stereochemical concept that ligand coupling is a concerted process in which the configuration of the coupling ligand is retained, as previously observed in many cases of reactions at a sulfur atom [2][3][4][5][6] and also at a copper atom [1, [18][19][20][21][22][23]. Additional stereochemical studies on hypervalent phosphorus intermediates are currently in progress in these laboratories.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Interestingly, Seyferth et al carried out similar reactions using both cisand trans-propenyllithium reagents and obtained only cisand trans-propenylbenzenes, respectively [8]. This observation is in accordance with our stereochemical concept that ligand coupling is a concerted process in which the configuration of the coupling ligand is retained, as previously observed in many cases of reactions at a sulfur atom [2][3][4][5][6] and also at a copper atom [1, [18][19][20][21][22][23]. Additional stereochemical studies on hypervalent phosphorus intermediates are currently in progress in these laboratories.…”
Section: Resultssupporting
confidence: 86%
“…When tris(2-pyridyl)phosphine oxide (Ia) was treated with an equivalent of an organometallic reagent in refluxing THF, 2,2'-bipyridyl (2a) was the major product, 2-substituted pyridines (3) and (4) and pyridine (Equation 3) also being formed. In the reactions of 2-pyridyl sulfoxides and p-benzenesulfonylphenyl sulfoxides with organometallic compounds, both 2-pyridyl andp-benzenesulfonylphenyl groups couple preferentially with the benzylic Grignard reagent [2][3][4][5][6][24][25][26].…”
Section: With Organometallic Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…An important feature of the coupling is whether it proceeds by a concerted process. This was experimentally confirmed previously by the observation that a substrate having a chiral carbon bonded to the sulfoxide group reacted with an alkylmagnesium halide to give the coupling product 5 [3] of a single stereoisomer or a mixture of diastereomers, we now have examined the chemical behavior of the optically active diastereomers 7a and 7b having adjacent chiral carbon and sulfur atoms in the ligand coupling reaction, and we have obtained results that are similar but much clearer from a stereochemical viewpoint then found in the previous studies [ 3 , 41. We also found that the ligand exchange reaction proceeds with retention of configuration at the CY carbon center but in an equilibrium giving a 3 : 1 mixture of diastereomers with respect to the sulfur stereocenter.…”
Section: Introductionsupporting
confidence: 59%
“…The concept [ 11 of the ligand coupling reaction at various heteroatoms [ 1,2], especially the reactivity of the central sulfur atom in a sulfurane, has successfully been developed through investigation of the reactions of sulfoxides, one class of tri-coordinate sulfur compounds. Also, similar reactions of organometallic reagents have been studied in detail DI.…”
Section: Introductionmentioning
confidence: 99%